Analisis Faktor-Faktor Kerentanan Banjir Pesisir (Studi pada Pesisir Pantai Utara Jawa Tengah) - Salim, M. Afif; Wahyudi, S. Imam; Wibowo, Kartono (Proceedings Series on Physical & Formal Sciences, 2023)
Flooding is a natural phenomenon that occurs in Indonesia, including the coastal areas of Pantura) which are complicated problems for the government that have not been fully handled properly. Pantura coastal flooding occurs due to rainwater flooding and tidal flooding, causing vulnerability. This study aims to determine the factors that cause vulnerability and determine the adaptation strategy for Pantura coastal flooding. This type of research is quantitative research because research is in the form of case studies based on descriptive assessments and the existence of quantitative data based on numbers and research is carried out by observation and data collection using data collection techniques and data analysis with SPSS Version 25.00 with 183 respondents. The research location is the coastal area of Pantura. Primary data collection method with questionnaires, interviews, observations, and documentation,. Based on the results of the study, the factors of coastal flood vulnerability are classified into physical vulnerability of buildings and infrastructure, biophysical and hydrological vulnerability, vulnerability of community capability and safety and flood vulnerability. The validity test of the vulnerability of coastal flooding shows all valid and reliable indicators because it has a validity value of > 0.300 and the reliability test value of the cronbrach alpha research instrument is above 0.700.